Optical absorption enhancement in slanted silicon nanocone hole arrays for solar photovoltaics - 张淑媛 刘雯 李兆峰 刘敏 刘雨生 王晓东 杨富华 (Chinese physics B, 2016)
We investigate slanted silicon nanocone hole arrays as light absorbing structures for solar photovoltaics via simulation.With only 1-μm equivalent thickness, a maximum short-circuit current density of 34.9 m A/cm~2 is obtained. Moreover, by adding an Ag mirror under the whole structure, a short-circuit current density of 37.9 m A/cm~2 is attained. It is understood that the optical absorption enhancement mainly results from three aspects. First, the silicon nanocone holes provide a highly efficient antireflection effect. Second, after breaking the geometric symmetry, the slanted silicon nanocone hole supports more resonant absorption modes than vertical structures. Third, the Fabry–Perot resonance enhances the light absorption after adding an Ag mirror.